Hizbul Wathan Dalam Meningkatkan Kedisiplinan dan Solidaritas Siswa SMK Muhammadiyah 2 Karanganyar - Damar Hardiansah; Mutohharun Jinan (Jayapangus Press, 2026)
The development of globalization and digital technology brings new challenges in the formation of students' character, especially in the aspects of discipline and social solidarity. This requires schools to present character education strategies that are able to provide direct social experiences to students. This study aims to analyze the role of Hizbul Wathan extracurricular activities in improving student discipline and solidarity at SMK Muhammadiyah 2 Karanganyar. This study uses a qualitative approach. Data were obtained through participatory observation, in-depth interviews, and documentation studies with informant 1 Hizbul Wathan mentor who actively participated in the activity. The results showed that Hizbul Wathan activities were able to shape student discipline through routine habits such as timely roll calls, neat attributes, and compliance with activity rules. In addition, the implementation of the team system and the learning by doing method were able to increase solidarity, cooperation, empathy, and a sense of responsibility among students through direct experience in group activities. This study also found that the success of internalizing character values ​​was influenced by the mentor's role model, consistency of habits, and active involvement of students in activities. Despite the obstacles in the form of the influence of digital technology, low initial awareness of students, and limited time for extracurricular activities, overall Hizbul Wathan has proven to be effective as a character education medium in forming students who are disciplined, independent, and have a high level of social awareness.